Los olvidados: Non-BRCA variants associated with Hereditary breast cancer in Mexican population - Dione Aguilar; María Lourdes Garza-Rodríguez; Carolina Elizabeth Muñiz-Garza; Fernando Alcorta Nuñez; Cynthia Mayte Villarreal-Garza; Oscar Vidal-Gutiérrez; Diana Cristina Pérez-Ibave; Carlos Horacio Burciaga-Flores (Breast Cancer Research)
Abstract Background Hereditary predisposition to breast and ovarian cancer syndrome (HBOC) is a pathological condition with increased cancer risk, including breast (BC), ovarian cancer (OC), and others. HBOC pathogenesis is caused mainly by germline pathogenic variants (GPV) in BRCA1 and BRCA2 genes. However, other relevant genes are related to this syndrome diagnosis, prognosis, and treatment, including TP53, PALB2, CHEK2, ATM, etc. This study aimed to identify the prevalence of non-BRCA genes in HBOC patients of Northeast Mexico. Methods This multicentric study included 1285 patients with HBOC diagnosis from four oncologic centers in northeast Mexico from 2016 to 2023. Genomic and clinical data were analyzed based on multi-gene panel results and electronic records of the medical geneticist consultation. For the data analysis of qualitative and quantitative variants, JASP statistical software (version 0.18.1) was used, taking p < 0.05 as a significant result. Results We found that 32.7% of the patients had at least one GPV in non-BRCA genes. The five most frequent non-BRCA genes were CHEK2, PALB2, MUTYH, CDKN2A, and ATM. Among the group of non-BRCA genes, six are involved in the homologous repair pathway (HR), and three are related to DNA damage repair (DDR) pathways. In analyzing GPVs in molecular pathways, both have similar frequencies with no statistical difference for BC. Conclusion Multi-gene testing implementation improves the detection of often overlooked genes related to HBOC pathogenesis and treatment. Non-BRCA GPVs in Northern Mexico correspond to one-third of the HBOC cases, including HR and DDR pathways genes that would be misdiagnosed if not tested. HR patient carriers are potential targets of iPARP therapies. The optimal approach to cancer treatment for non-BRCA mutation carriers warrants further investigation to develop newer therapies.